Epstein-Barr virus primary infection in healthy children - Mónica García-Peris; M. Isabel Jiménez Candel; Yolanda Mañes Jiménez; Macarena Pariente Martí; Damiana González Granda; Fernando Calvo Rigual (Elsevier, 2019)
Introduction: The aim of this study is to assess epidemiological, clinical and laboratory characteristics of primary infection by Epstein-Barr virus (EBV) in children without previous diagnosis of any immune disease and its relationship with clinical presentation. Patients and methods: A retrospective study was conducted on all children from 0 to 15 years with IgM against viral capsid of EBV positive or indeterminate during a 22 month period. Epidemiological, clinical and laboratory data were analysed and compared between typical (mononucleosis syndrome) and non-typical clinical symptoms. Results: The study included a total of 103 children, with a median age of 7 years (3-12.5 years). Almost two-thirds (63%) of patients had typical clinical signs, with a mononucleosis syndrome, and 37% had a non-typical presentation. The non-typical clinical group had a lower age (P = .03) and took less antibiotic than the typical clinical group (P = .015). From laboratory studies, there were no differences between the groups, except in RCP, which was higher in typical clinical group (P = .04). Heterophile antibodies were positive in 33% of patients. An indeterminate IgM against viral capsid was present in 20% of the patients, and most of them had an oligosymptomatic or atypical presentation. An IgM positive for other viruses was found in 21%, and 3 of them were suspicious of false positive for EBV. Conclusions: In the studied population, a primary infection due to EBV is common in younger ages, and they have usually an oligosymptomatic clinical presentation. A very low percentage of positive heterophile antibodies were found. Cases with indeterminate IgM against viral capsid are more frequent in the non-typical clinical group. Co-infection with other viruses is common. Resumen: Introducción: El objetivo de este estudio es conocer las características epidemiológicas, clínicas y analíticas de la primoinfección por el virus de Epstein-Barr (VEB) en niños sin diagnóstico previo de ninguna enfermedad inmune y su relación con la forma de presentación clínica. Pacientes y métodos: Estudio retrospectivo de pacientes entre 0 y 15 años con IgM sérica frente a la cápside viral del VEB positiva o indeterminada, durante un período de 22 meses. Se analizaron datos epidemiológicos, clínicos y de laboratorio y se compararon según tuvieran una clínica típica (síndrome mononucleósico) o no típica. Resultados: Se incluyeron 103 niños. La mediana de la edad fue de 7 años (3-12.5 años). El 63% de los pacientes presentaron clínica típica o síndrome mononucleósico y el 37% una clínica no típica. La edad fue significativamente menor en el grupo de clínica no típica (p = 0,03) y recibieron menos tratamiento antibiótico (p = 0,015). En los parámetros analíticos no hubo diferencias estadísticamente significativas excepto en la PCR, discretamente más elevada en el grupo de clínica típica (p = 0,04). El 33% de los pacientes tuvieron anticuerpos heterófilos positivos. El 20% tuvieron una IgM frente a la cápside viral indeterminada, la mayoría con clínica oligosintomática o atípica. El 21% tuvieron IgM positivas para otros virus y 3 de ellos fueron posibles falsos positivos para el VEB. Conclusiones: En nuestra población, la primoinfección por VEB es frecuente en niños de menor edad, y en ellos predominan las formas oligosintomáticas. El porcentaje de anticuerpos heterófilos positivos ha sido muy bajo en nuestra muestra. Los casos con IgM frente a la cápside viral indeterminada son más frecuentes en el grupo de clínica no típica. Es común detectar coinfección con otros virus.